2019
DOI: 10.1001/jamainternmed.2018.5406
|View full text |Cite
|
Sign up to set email alerts
|

Association of Long-term Exercise Training With Risk of Falls, Fractures, Hospitalizations, and Mortality in Older Adults

Abstract: IMPORTANCE Long-term exercise benefits on prevalent adverse events in older populations, such as falls, fractures, or hospitalizations, are not yet established or known. OBJECTIVE To systematically review and investigate the association of long-term exercise interventions (Ն1 year) with the risk of falls, injurious falls, multiple falls, fractures, hospitalization, and mortality in older adults. DATA SOURCES PubMed, Cochrane Central Register of Controlled Trials, SportDiscus, PsychInfo, and Ageline were search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
3
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 79 publications
6
87
3
8
Order By: Relevance
“…Exercise is the only strategy that can improve multiple modifiable musculoskeletal fracture risk factors, but appropriate prescription and adherence is critical. Meta‐analyses and systematic reviews of exercise intervention trials have reported that well‐controlled, supervised, and structured programs involving multicomponent exercise training, incorporating moderate‐ to high‐intensity progressive resistance training (PRT) with short bouts of varied or diverse loading weight‐bearing impact activities and challenging balance and mobility exercises, can improve or maintain BMD and multiple fall‐related risk factors in older adults . However, several real‐world, translational studies examining the effects of exercise programs delivered to older people and those with osteoporosis in community settings have reported mixed findings on bone and muscle outcomes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise is the only strategy that can improve multiple modifiable musculoskeletal fracture risk factors, but appropriate prescription and adherence is critical. Meta‐analyses and systematic reviews of exercise intervention trials have reported that well‐controlled, supervised, and structured programs involving multicomponent exercise training, incorporating moderate‐ to high‐intensity progressive resistance training (PRT) with short bouts of varied or diverse loading weight‐bearing impact activities and challenging balance and mobility exercises, can improve or maintain BMD and multiple fall‐related risk factors in older adults . However, several real‐world, translational studies examining the effects of exercise programs delivered to older people and those with osteoporosis in community settings have reported mixed findings on bone and muscle outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses and systematic reviews of exercise intervention trials have reported that well-controlled, supervised, and structured programs involving multicomponent exercise training, incorporating moderate-to high-intensity progressive resistance training (PRT) with short bouts of varied or diverse loading weight-bearing impact activities and challenging balance and mobility exercises, can improve or maintain BMD and multiple fall-related risk factors in older adults. (4)(5)(6) However, several realworld, translational studies examining the effects of exercise programs delivered to older people and those with osteoporosis in community settings have reported mixed findings on bone and muscle outcomes. (7,8) Thus, there remains a need for safe, effective, accessible, evidence-based exercise programs that can be widely adopted, implemented, and maintained in the community for people with or at increased risk for fractures.…”
Section: Introductionmentioning
confidence: 99%
“…-Physical therapy: Physical activity is beneficial for reducing overall morbidity and mortality in older adults (36). Exercise tended to decrease mortality risk in clinical populations (mostly people with cognitive decline or cardiac disease), which reinforces the role of exercise as a core therapeutic element for treating prevalent diseases in older people (37). Tolerance of cardiac muscle to effortinduced ischemia could be increased by using antioxidant and cardio-protective agents (38).…”
Section: Rehabilitation Interventions For Neurologic Elderly Patientsmentioning
confidence: 88%
“…Dynamic balance training can involve slow movements in single stance, simple tai chi movements, tandem walking, turns while walking, walking backwards, walking over a virtual object (eg, a 15-cm stripe on the floor), slow forward lunges, and slow dance movements. Multicomponent balance training is probably most effective in improving balance (40) The best exercise regimen in older people would be moderate-intensity, multicomponent training comprising balance exercises (eg, balance, strength training for the lower limbs, and aerobic exercisewalking), performed 2 to 3 times per week, with 30 to 60 minutes (37).…”
Section: Rehabilitation Interventions For Neurologic Elderly Patientsmentioning
confidence: 99%
“…However, recently there was a review and meta-analysis that showed exercise had a beneficial effect on reduction of fall-related fractures, with pooled estimates of RR 0.604, alongside improvements in leg strength 11 . Interestingly, one recent review of long term exercise (≥1 year) in older people has also found a significant reduction in fracture 12 . Bone mineral density (BMD) is weakly associated with fracture risk 13 , but combined with a history of falls, becomes important in terms of fracture prevention.…”
Section: Introductionmentioning
confidence: 99%